Repurposing the Open Global Health Library for the discovery of novel Mpro destabilizers with scope as broad-spectrum antivirals - Castillo, Francisco; Ramírez, David; Ramos, María C.; Martinez-Arribas, Blanca; Domingo-Contreras, Elisabeth; Mackenzie, Thomas A.; Peña-Varas, Carlos; Lindemann, Sven; Montero, Fernando; Annang, Fredderick; Vicente, Francisca; Genilloud, Olga; et al. (Frontiers in Pharmacology, 2024)
The SARS coronavirus 2 (SARS-CoV-2) epidemic remains globally active. The emergence of new variants of interest and variants of concern (VoCs), which are potentially more vaccine-resistant and less sensitive to existing treatments, is evident due to their high prevalence. The prospective spread of such variants and other coronaviruses with epidemic potential demands preparedness that can be met by developing fast-track workflows to find new candidates that target viral proteins with a clear in vitro and in vivo phenotype. Mpro (or 3CLpro) is directly involved in the viral replication cycle and the production and function of viral polyproteins, which makes it an ideal target. The biological relevance of Mpro is highly conserved among betacoronaviruses like HCoV-OC43 and SARS-CoV-2, which makes the identification of new chemical scaffolds targeting them a good starting point for designing broad-spectrum antivirals. We report an optimized methodology based on orthogonal cell-free assays to identify small molecules that inhibit the binding pockets of both SARS-CoV-2-Mpro and HCoV-OC43-Mpro; this blockade correlates with antiviral activities in HCoV-OC43 cellular models. By using such a fast-tracking approach against the Open Global Health Library (Merck KGaA), we have found evidence of the antiviral activity of compound OGHL98. In silico studies dissecting intermolecular interactions between OGHL98 and both proteases and comprising docking and molecular dynamics simulations (MDSs) concluded that the binding mode was primarily governed by conserved H-bonds with their C-terminal amino acids and that the rational design of OGHL98 has potential against VoCs proteases resistant to current therapeutics.